2021
DOI: 10.1177/23312165211014437
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Influence of Noise Reduction on Listening Effort in Hearing-Impaired Listeners Using Response Times to an Arithmetic Task in Noise

Abstract: Single microphone noise reduction (NR) in hearing aids can provide a subjective benefit even when there is no objective improvement in speech intelligibility. A possible explanation lies in a reduction of listening effort. Previously, we showed that response times (a proxy for listening effort) to an auditory-only dual-task were reduced by NR in normal-hearing (NH) listeners. In this study, we investigate if the results from NH listeners extend to the hearing-impaired (HI), the target group for hearing aids. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Studies related to the use of hearing aids ( Qian et al, 2016 ; Bucholc et al, 2022 ) and cochlear implants ( Mertens et al, 2021 ) have demonstrated that as hearing aids and cochlear implants help to restore auditory perception, the onset of CI is delayed. It is hypothesized that hearing aids ( Reinten et al, 2021 ) and cochlear implants ( Chatterjee et al, 2023 ) improve the “effortful process” of sound discrimination in the daily lives of SNHL patients, and that this change reduces the previous over-allocation of cognitive resources, helping to restore balance in the CL.…”
Section: Hypothesismentioning
confidence: 99%
“…Studies related to the use of hearing aids ( Qian et al, 2016 ; Bucholc et al, 2022 ) and cochlear implants ( Mertens et al, 2021 ) have demonstrated that as hearing aids and cochlear implants help to restore auditory perception, the onset of CI is delayed. It is hypothesized that hearing aids ( Reinten et al, 2021 ) and cochlear implants ( Chatterjee et al, 2023 ) improve the “effortful process” of sound discrimination in the daily lives of SNHL patients, and that this change reduces the previous over-allocation of cognitive resources, helping to restore balance in the CL.…”
Section: Hypothesismentioning
confidence: 99%
“…Test-retest reliability of listening effort measures (e.g., dual-task, pupillometry) has been evaluated using a variety of analyses: most commonly intraclass correlation coefficient (ICC) and Pearson's product moment correlation. 16,[45][46][47][48][49][50] Importantly, these two calculations measure relative reliability, not absolute reliability. Relative reliability describes the measurement's ability to rank order individuals under conditions of repeated measurement-providing a statistic of the variability of participants in a study.…”
Section: Test-retest Reliability and Accounting For Measurement Errormentioning
confidence: 99%